Conservation of an Early Electric Master Clock: Making a Copy as a Conservation Tool - Françoise Collanges (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
The project was to research how the making of a copy could contribute to the study and conservation of an electric master clock, c. 1855, by Constantin Detouche and Jean-Eugene Robert-Houdin. A copy of the clock was produced as well as an electric cell similar to the one used in 1855 and they were both tested, which made possible to determine how to safely run the original clock.